Effects of illuminance and contrast on the reading of Chinese text by myopes. (November 2020) - Bao, J; Tan, R; Huo, J; Drobe, B; Chen, H
Twenty-four young adults with myopia in both eyes and no anisometropia participated in this study. Observers were instructed to read one A4-sized page of Chinese text at different levels of illuminance and text contrast, while their reading distance, head tilt angle and reading speed were recorded using an electromagnetic motion tracking system. Four illuminances (3, 30, 300 and 600 lx) and two text contrast levels (90% and 45%) were tested in randomised order. Observers tended to shorten their reading distance and increase their head tilt angle when reading at low illuminance. In addition, their reading speed was markedly slower at low illuminance and low contrast. These effects were found for both text contrast conditions but were greater at low contrast. Illuminance and text contrast play a critical role in myope's reading behaviour. An illuminance of 300 lx or more with high-contrast text allows for good reading posture and rapid reading of Chinese text.